CREATION AND MAINTENANCE OF THE CAREER WEB PORTFOLIO OF STUDENTS: PROBLEMS AND SOLUTIONS - Aleksey M. Gostin; Svetlana V. Panyukova (Moscow Polytechnic University, 2016)
The article is devoted to students' web-portfolio technologies, which enable to present the results of students' academic activities to employers and to monitor job placement and career development of graduates. The article discusses the benefits and possibilities of aspecial social network 4portfolio.ru for designing web-portfolio of students and teachers.